Moral distress, coping mechanisms, and turnover intent among healthcare providers in British Columbia: a race and gender-based analysis - Jorge Andrés Delgado-Ron; Muhammad Haaris Tiwana; Alice Murage; Rosemary Morgan; Simran Purewal; Julia Smith (BMC, 2024)
Abstract Background This study explores intersectionality in moral distress and turnover intention among healthcare workers (HCWs) in British Columbia, focusing on race and gender dynamics. It addresses gaps in research on how these factors affect healthcare workforce composition and experiences. Methods Our cross-sectional observational study utilized a structured online survey. Participants included doctors, nurses, and in-home/community care providers. The survey measured moral distress using established scales, assessed coping mechanisms, and evaluated turnover intentions. Statistical analysis examined the relationships between race, gender, moral distress, and turnover intention, focusing on identifying disparities across different healthcare roles. Complex interactions were examined through Classification and Regression Trees. Results Racialized and gender minority groups faced higher levels of moral distress. Profession played a significant role in these experiences. White women reported a higher intention to leave due to moral distress compared to other groups, especially white men. Nurses and care providers experienced higher moral distress and turnover intentions than physicians. Furthermore, coping strategies varied across different racial and gender identities. Conclusion Targeted interventions are required to mitigate moral distress and reduce turnover, especially among healthcare workers facing intersectional inequities.